2022
DOI: 10.3389/fpls.2022.912637
|View full text |Cite
|
Sign up to set email alerts
|

Combining GWAS, Genome-Wide Domestication and a Transcriptomic Analysis Reveals the Loci and Natural Alleles of Salt Tolerance in Rice (Oryza sativa L.)

Abstract: Soil salinity poses a serious threat to the sustainable production of rice (Oryza sativa L.) throughout the world. Thus, the detection of loci and alleles responsible for salt tolerance is fundamental to accelerating the improvement of rice and producing the resilient varieties that will ensure future harvests. In this study, we collected a set of 191 mini-core rice populations from around the world, evaluated their salt tolerance based on plant growth and development phenotypes at the seedling stage, and divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…Soil salinity increase is mainly owed to improper irrigation practices and limited fresh water irrigation [75]. Many farmers have had to use mixed saline water for irrigating their crops cultivated in the fertile soil of the Nile Delta and Valley, practices that imposed negative effects on both soil properties and crop productivity.…”
Section: Practical Implications Of This Studymentioning
confidence: 99%
“…Soil salinity increase is mainly owed to improper irrigation practices and limited fresh water irrigation [75]. Many farmers have had to use mixed saline water for irrigating their crops cultivated in the fertile soil of the Nile Delta and Valley, practices that imposed negative effects on both soil properties and crop productivity.…”
Section: Practical Implications Of This Studymentioning
confidence: 99%
“…In addition, transcriptomic sequencing provides a high-throughput approach to identifying differentially expressed genes (DEG) at the whole genome level. The combination of transcriptome and genome-wide association analysis has been confirmed to be an effective method for identifying causative or candidate genes regulating complicated quantitative traits ( Li et al., 2021 ; Liu et al., 2021 ; Lv et al., 2022 ; Tan et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since this initial observation, various studies have shown increased DHPD transcription in rice under abiotic stress ( Shankar et al., 2016 ; Zhou et al., 2016 ; Li et al., 2018 ). DHPD is one of seven genes that were simultaneously selected for salt tolerance during domestication of rice, that were identified by Lv et al. (2022) in transcriptomics and genome wide association studies of wild and domesticated Asian and African rice.…”
Section: Discussionmentioning
confidence: 99%
“…Since this initial observation, various studies have shown increased DHPD transcription in rice under abiotic stress (Shankar et al, 2016;Zhou et al, 2016;Li et al, 2018). DHPD is one of seven genes that were simultaneously selected for salt tolerance during domestication of rice, that were identified by Lv et al (2022) in transcriptomics and genome wide association studies of wild and domesticated Asian and African rice. Narsai and coworkers found that in rice, DHPD was one of 10% -14% of differentially expressed genes upregulated in response to salt and drought that was also upregulated in A. thaliana (Narsai et al, 2010).…”
mentioning
confidence: 99%